1993
DOI: 10.1161/01.atv.13.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Substrate delivery as a determinant of hepatic apoB secretion.

Abstract: L ipoprotein levels in plasma are a function of the rate at which they are produced as well as the rate at which they are catabolized. Both processes are critical. Yet the greatest proportion of clinical investigative energy by far has focused on the latter, with relatively little interest, by contrast, in the former. To be sure, considerable work has been done by basic scientists to elucidate the steps involved in the formation and secretion of a hepatic particle (for a general review, see Reference 1). Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(81 citation statements)
references
References 91 publications
(40 reference statements)
2
79
0
Order By: Relevance
“…33 Furthermore, an effect of this kind would have delayed peak TAG concentrations during the walking trials Ð something we did not observe. There could be decreased hepatic VLDL-TAG secretion during the walking trials but plasma concentrations of NEFA and insulin, both important in¯uences on this, 34 did not differ between trials.…”
Section: Discussionmentioning
confidence: 83%
“…33 Furthermore, an effect of this kind would have delayed peak TAG concentrations during the walking trials Ð something we did not observe. There could be decreased hepatic VLDL-TAG secretion during the walking trials but plasma concentrations of NEFA and insulin, both important in¯uences on this, 34 did not differ between trials.…”
Section: Discussionmentioning
confidence: 83%
“…There is no evidence at present as to whether distinct TAG pools are preferentially utilized for the ' first ' and ' second ' step phases of incorporation of TAG into the hydrophobic core of VLDL. If they were to be so used, then the existence of separate routes for TAG secretion would enable control to be exerted on the number and size of the secreted particles, and thus allow these parameters to be differentially affected by the supply of fatty acid and carbohydrate substrates to the liver [130,131]. Insulin is known to decrease the availability of apoB for secretion by increasing the rate of early degradation of the newly synthesized protein (see [132]).…”
Section: Figure 4 Dual Routes May Be Involved In the Incorporation Ofmentioning
confidence: 99%
“…Insulinenhanced degradation only affects a proportion of total apoB and appears to have different characteristics from constitutive degradation [113,140]. However, it is not known whether it is the availability of apoB that determines the fraction of TAG that is channelled towards secretion, or vice versa ; evidently increases in TAG secretion can occur in the absence of any increase in apoB secretion [130]. From experiments conducted on cultured hepatocytes obtained from fed or starved rats, Davis et al [171] concluded that the availability of apoB %) , which is the major B apoprotein in rat liver, determines the rate of TAG secretion.…”
Section: Partitioning Of Tag Between Secretion and Retention In The Lmentioning
confidence: 99%
“…In vitro and in vivo studies have established that increased delivery of NEFA or uptake of triglyceriderich remnants to the liver will cause the secretion rate of VLDL particles to increase [21,22]. An increased secretion rate of VLDL will result in the increased generation of LDL particles.…”
Section: Consequences Of An Impaired Asp Pathwaymentioning
confidence: 99%